Expression of ionotropic receptors in terrestrial hermit crab's olfactory sensory neurons - Groh-Lunow, Katrin C.; Getahun, Merid N.; Grosse-Wilde, Ewald; Hansson, Bill S. (Frontiers in Cellular Neuroscience, 2015)
Coenobitidae are one out of at least five crustacean lineages which independently succeeded in the transition from water to land. This change in lifestyle required adaptation of the peripheral olfactory organs, the antennules, in order to sense chemical cues in the new terrestrial habitat. Hermit crab olfactory aesthetascs are arranged in a field on the distal segment of the antennular flagellum. Aesthetascs house approximately 300 dendrites with their cell bodies arranged in spindle-like complexes of ca. 150 cell bodies each. While the aesthetascs of aquatic crustaceans have been shown to be the place of odor uptake and previous studies identified ionotropic receptors (IRs) as the putative chemosensory receptors expressed in decapod antennules, the expression of IRs besides the IR co-receptors IR25a and IR93a in olfactory sensory neurons (OSNs) has not been documented yet. Our goal was to reveal the expression and distribution pattern of non-co-receptor IRs in OSNs of Coenobita clypeatus, a terrestrial hermit crab, with RNA in situ hybridization. We expanded our previously published RNAseq dataset, and revealed 22 novel IR candidates in the Coenobita antennules. We then used RNA probes directed against three different IRs to visualize their expression within the OSN cell body complexes. Furthermore we aimed to characterize ligand spectra of single aesthetascs by recording local field potentials and responses from individual dendrites. This also allowed comparison to functional data from insect OSNs expressing antennal IRs. We show that this orphan receptor subgroup with presumably non-olfactory function in insects is likely the basis of olfaction in terrestrial hermit crabs.